Soil nutrient status of slope lands under hevea brasiliensis in Mizoram at varying altitudes and their relationship with soil properties - Satisha G C; Dey S K; Pal T K; Varghese Y A (Indian Journal of Natural Rubber Research, 2000)
The status of nutrients in the soils of slope lands under Hevea brasiliensis in Mizoram at different altitudes (100-750 m above mean sea level) was determined for better understanding of nutrient availability and crop productivity. The soils were low to medium in available nitrogen. About 74 per cent of the soils could be rated as deficient in Bray's-P. The total and available N, P and K contents, in general, was in the order of K>N>P. The soils contained adequate to toxic amounts of DTPA extractable Fe, Mn, Cu and tested low in available Zn especially for soils of higher elevation. Total and available N and P and DTPA extractable Zn had a significant negative relationship with altitude whereas DTPA-Fe and cu were positively related. There was positive influence of silt on total N and of both organic carbon and silt on KNnO4-N. The total and Bray's-P were significantly positively related with pH, silt and clay content. The NH4OAc-K was positively related with CEC. The silt and clay contents had negative influence on DTPA extractable Fe and Cu while DTPA-Zn was positively related with silt, clay and pH.
Keywords: Altitude; Altitude; Hevea brasiliensis; Hevea brasiliensis; Mizoram; Mizoram; Slope lands; Slope lands; Soil characteristics; Soil characteristics; Soil nutrients; Soil nutrients